Development of a prototype automatic sauce dispenser / Asif Muhaimin Mohd Saiful Nizam - Mohd Saiful Nizam, Asif Muhaimin (2023)
Automatic Sauce Dispenser is an engineering solution project to fix the problems that exist with typical type of manual sauce dispenser. Automatic sauce dispenser is an automated sauce dispenser that is fast, accurate and aesthetically pleasing. Due to the difficulty for user to dispense sauce using manual sauce dispenser, this project was proposed to develop the Automatic sauce dispenser that will dispense sauce automatically control by the controlling system. This project intends to design, analyze and fabricate an Automatic Sauce Dispenser that able to dispense automatically as it detects the cup. The Automatic Sauce Dispenser is a machine that can speed up the process for user to dispense the sauce because it is more efficient and less time consumable. In conclusion, the Automatic Sauce Dispenser will benefit the fast-food restaurant because to reduce time consuming and increase hygiene surrounding area